2022
DOI: 10.7759/cureus.28570
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglossal Duct Cyst Carcinoma With Synchronous Thyroid Papillary Carcinoma: A Case Report and Literature Review

Abstract: Thyroglossal duct cysts (TGDC) are one of the most common congenital anomalies in the neck. Malignant transformation of these cysts is rare and synchronous involvement of the thyroid gland is even rarer. We report a case of synchronous occurrence of carcinoma in the thyroglossal duct cyst and thyroid gland and review the relevant literature. A 24-year-old woman who presented with a midline cervical mass, clinical examination, and complementary study was suggestive of a thyroglossal cyst with papillary carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[11] Currently, radioactive iodine therapy is only recommended for thyroglossal duct cancer in combination with ipsilateral thyroid cancer and lymph node metastases. [23] The most common genetic mutation in thyroid cancer is the BRAF mutation, which accounts for about 45% of papillary thyroid cancers, [32] and the most common BRAF family variant in thyroid cancer is BRAF V600E in the BRAF1 gene. Some studies have also shown that patients with BRAF mutations should be routinely treated with I 131 after surgery to reduce the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Currently, radioactive iodine therapy is only recommended for thyroglossal duct cancer in combination with ipsilateral thyroid cancer and lymph node metastases. [23] The most common genetic mutation in thyroid cancer is the BRAF mutation, which accounts for about 45% of papillary thyroid cancers, [32] and the most common BRAF family variant in thyroid cancer is BRAF V600E in the BRAF1 gene. Some studies have also shown that patients with BRAF mutations should be routinely treated with I 131 after surgery to reduce the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The former is primarily employed for the treatment of malignant transformation of the ectopic thyroid gland within the thyroglossal cyst and is the main surgical procedure performed in clinical practice with a low postoperative recurrence rate of only 3%. [23] The key steps of this procedure include excising the cyst and cancerous tissue, removing the hyoid bone, and eliminating the core tissue around the lingual bundle of the thyroid near the blind foramen from the lingual muscle. [24] The latter approach is typically used in cases where there is metastasis of ipsilateral thyroid cancer to the ectopic thyroid gland within the ipsilateral thyroglossal hyoid bone or in the presence of multiple thyroid cancers.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…The classic Sistrunk surgery began to be performed in 1920, and comprises resection of the thyroglossal duct cyst, fistula tract, middle segment of the hyoid bone and surrounding tissue of the tongue muscle (18). At present, Sistrunk surgery has become the standard surgical treatment for thyroglossal duct cyst and can reduce the recurrence rate to 3% (19). As malignancies in thyroglossal duct cysts are rarely identified preoperatively, most thyroglossal duct carcinomas are initially treated surgically as benign tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Карциномът на тиреоглосния канал е много рядко събитие, с едва неколкостотин докладвани случая в литературата след първото му описание от Брентано през 1911 г. (18). Честотата на първичния карцином в тиреоглосалния канал в литературата варира от 0,7% до 1,6% (19).…”
Section: обсъжданеunclassified